Suitability of the Physical Properties of Soil for Crop Production: A Study in Tangail Sadar - Mamun, SA; Rahman, F; Yeasmin, F; Islam, MA (Journal of Environmental Science and Natural Resources, 2012)
Use of imbalanced chemical fertilizer and changing crop and cropping pattern are becoming a serious threat for the sound environment of the soil. The study provided an assessment of the present status of soil quality of Tangail Sadar based on the laboratory analysis of physical parameters such as bulk density, water holding capacity, sand, silt and clay percentage from July, 2010 to December, 2010. 40 soil samples from 20 different places were collected from 0-15 cm and 15-30 cm depth of the soil from 5 locations mentioned as Porabari, Santosh, Gharinda, By-pass and Ashekpur. The study conducted revealed that among the 40 soil samples, 30 soil's textural classes are sandy clay loam, 7 are sandy clay and rests 3 are clay loam and the pH value ranges from 5.3 to 6.4. The comparative analysis shows that the average texture class is sandy clay loam, which is not relevant to the standard level because the standard texture class is loamy. The average moisture percentage, bulk density and water holding capacity are found 2.865 %, 0.0926 gm/cm3 and 9.44% respectively which are almost similar to standard values and almost soil are suitable for plant growth. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10160 J. Environ. Sci. & Natural Resources, 4(2): 121-125, 2011